BISOPROLOL EFFICACY IN PATIENTS WITH ARTERIAL HYPERTENSION ASSOCIATED WITH CARDIOPULMONARY DISEASES - G. N. Gorokchovskaya; M. M. Petina (Рациональная фармакотерапия в кардиологии, 2016)
Beta-blockers application in modern cardiologic practice is reviewed with focus on beta-blocker advantages in treatment of patients with arterial hypertension associated with ischemic heart disease. Bisoprolol usage specifics caused by its pharmacokinetics and a pharmacodynamics are specially considered. Bisoprolol advantages in patients with chronic heart failure and a chronic obstructive pulmonary disease are presented. All data are supported by results of randomized clinical trails.